Trust in African feminist teaching and learning practices: Conscientisation and connection - Knowles, Corinne (Critical Studies in Teaching and Learning, 2025)
In higher education, trust is possible (or not) based on the dynamic between different components and people in the university. This paper considers the relationship between students and their lecturer in the context of a neoliberal ethos. Using an African feminist lens, the close-up, self-study of a postgraduate course in Political and International Studies at Rhodes University is examined for its intentions and transgressions to determine how trust can be built and ruptured. Two ideas – ‘conscientisation’ and ‘connection’ – are theorised and then demonstrated through the reflections of the students and lecturer. Through a variety of mechanisms and processes, conscientisation and connection were intentionally built into how the course was run, and students’ reflections reveal their transformational capacity. The final assessment did, however, become a site of unraveling and contestation, and provided an opportunity to look more deeply into how robust these ideas can be in a setting that valorises individualism and competition.